Strategi Guru dalam Pengembangan Literasi Awal Anak Usia Dini - Siti Aisyah; Musa Musa (Center for Religious Studies and Social Empowerment Foundation, 2023)
This article reveals teacher strategies in developing early childhood literacy. This article originates from descriptive qualitative research. The results of the research show that the strategy used by teachers is learning strategies through singing and learning strategies through telling stories. The obstacles faced by teachers in developing early literacy are limited learning tools and media and lack of participation from parents. The teacher's effort to overcome the lack of parental participation is that every time the teacher reports are distributed, the teacher invites parents to come to school to discuss children's growth and development and provide an explanation of the importance of early literacy. The lack of literacy learning media and tools means that teachers have to be creative in creating literacy learning strategies, such as carrying out song activities, imitating the shapes of the letters of the alphabet, and creating literacy lessons using fun educational games. Artikel ini mengungkap strategi guru dalam pengembangan literasi awal anak usia dini. Artikel ini berasal dari penelitian kualitatif deskriptif. Hasil penelitian menunjukkan bahwa strategi yang digunakan guru adalah dengan melakukan strategi belajar melalui bernyanyi dan strategi belajar melalui bercerita. Kendala yang dihadapi guru dalam mengembangkan literasi awal adalah keterbatasan alat dan media pembelajaran dan kurangnya partisipasi dari orang tua. Upaya guru dalam mengatasi kurangnya partisipasti orang tua yaitu setiap pembagian rapor guru mengundang orangtua murid untuk hadir ke sekolah dalam rangka membahas tumbuh kembang anak serta memberikan penjelasan mengenai pentingnya literasi awal. Kurangnya media dan alat pembelajaran literasi membuat guru harus kreatif menciptakan sebuah strategi pembelajaran literasi, seperti melakukan kegiatan gerak lagu, menirukan bentuk huruf abjad, dan membuat pembelajaran literasi dengan menggunakan alat permainan edukatif yang menyenangkan.